A112 - power generation by ocean waves (ii) : electric generator (A) - Nur Muhammed Seah Kuan Yew (2018)
Fossil fuels are non-renewable resources and over reliance of fossil fuels create detrimental effect on the environment. Hence, the world needs to accelerate its search for an alternative energy sources. This project aims to explore different concepts of power generation by ocean waves and its feasibility in Singapore’s climate condition. The focus of this project is to study, design and fabricate a prototype based on the concept of the oscillating water column power conversion system. The prototype was examined by a series of experiments to improve its design. The results from the experiments were recorded and analysed in this report. Finally, with a better understanding of the concept, suggestions for improvement were made to the project so that it can benefit similar future projects.